2010
DOI: 10.1007/s11999-010-1471-9
|View full text |Cite
|
Sign up to set email alerts
|

Do Surgical Margin and Local Recurrence Influence Survival in Soft Tissue Sarcomas?

Abstract: Background Established prognostic factors influencing survival in soft tissue sarcomas include tumor stage, histopathologic grade, size, depth, and anatomic site. The presence of tumor near or at the margin of resection increases the risk of local recurrence but whether a positive surgical margin or local recurrence affect overall survival is controversial. Questions/purposes We explored the impact of microscopic margin on local recurrence, metastasis, and overall survival in patients with intermediate-to high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
101
4
13

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(132 citation statements)
references
References 28 publications
14
101
4
13
Order By: Relevance
“…Local recurrence rates have ranged considerably in previous reports, some of which can be attributed to varying inclusion and exclusion criteria and differences in the categorization of quantitative margin (Table 4). Our overall local recurrence rate of 3.4% for negative-margin patients with extremity soft tissue sarcoma echoes recent findings of other investigators [2,3,8,14,18,23,26]. Despite a number of reports suggesting a higher local recurrence rate associated with close margins of 1-2 mm or less [3,8,14,18], the rate of 4.4% in our study would suggest, as long as oncologic resection principles are followed and radiation is used judiciously, close margins can be tolerated to minimize morbidity and maximize function of the patient with limb salvage.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Local recurrence rates have ranged considerably in previous reports, some of which can be attributed to varying inclusion and exclusion criteria and differences in the categorization of quantitative margin (Table 4). Our overall local recurrence rate of 3.4% for negative-margin patients with extremity soft tissue sarcoma echoes recent findings of other investigators [2,3,8,14,18,23,26]. Despite a number of reports suggesting a higher local recurrence rate associated with close margins of 1-2 mm or less [3,8,14,18], the rate of 4.4% in our study would suggest, as long as oncologic resection principles are followed and radiation is used judiciously, close margins can be tolerated to minimize morbidity and maximize function of the patient with limb salvage.…”
Section: Discussionsupporting
confidence: 90%
“…However, the margin status of the patients lost to followup did not differ from the overall patient population. Third, the followup interval was shorter than some historical reports although previous literature has documented the risk of local recurrence decreases after 3 years and our median followup of 44 months compares favorably to existing literature [3,4,14,18]. Fourth, the pathologic specimens were not all evaluated by the same pathologist and were not rereviewed to ensure consistency in reporting.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Patients who develop a local recurrence from a soft-tissue sarcoma have a poor prognosis [1,7,8]. One study suggests the development of a local recurrence is the most important factor associated with decreased survival, and once patients develop a local recurrence, they are about three times more likely to die from disease compared to patients who do not develop a local recurrence [6].…”
Section: Introductionmentioning
confidence: 99%
“…One study suggests the development of a local recurrence is the most important factor associated with decreased survival, and once patients develop a local recurrence, they are about three times more likely to die from disease compared to patients who do not develop a local recurrence [6]. Novais et al [8] confirmed local recurrence independently predicts survival after adjusting for all major risk factors. Contemporary multimodal treatment of primary soft-tissue sarcoma reportedly reduces the incidence of local recurrence [1,6].…”
Section: Introductionmentioning
confidence: 99%